Signal Fingerprinting as a Novel Diagnostic Tool to Identify Conduction Inhomogeneity - Ye, Ziliang; van Schie, Mathijs S.; de Groot, Natasja M. S. (Frontiers in Physiology, 2021)
Background: Inhomogeneous intra-atrial conduction facilitates both initiation and perpetuation of atrial fibrillation (AF) and is reflected in electrogram (EGM) morphology. Objective: The primary objective of this study is to investigate regional differences in features of different EGM types during SR and to design a patient-specific signal fingerprint, which quantifies the severity and extensiveness of inhomogeneity in conduction. Methods: Patients (N=189, 86% male; mean age 65±9 years) undergoing coronary artery bypass grafting underwent high resolution mapping of the right atrium (RA), left atrium (LA), pulmonary vein area (PVA) including Bachmans bundle (BB). EGMs during 5 seconds of sinus rhythm (SR) were classified as single potentials (SP), short double potentials (SDP, interval between deflections <15 ms), long double potentials (LDP, deflection interval >15 ms) or fractionated potentials (FP, ≥3 deflections). Of all SPs, differences in relative R- and S-wave amplitude of all SPs were calculated (R/S ratios). Time difference between first and last deflection were determined (fractionation duration, FD) and potentials with amplitudes <1.0 mV were labeled as low voltage. Conduction block (CB) was defined as a difference in local activation time between adjacent electrodes of ≥12 ms. Results: A total of 1,9645,637 EGMs (9,331±3,336 per patient) were classified. RA BB PVA LA Median voltage(mV) 4.68 [3.43–5.72] 5.07 [3.16–6.99] 4.73[2.52–6.44] 5.54 [3.28–7.30] Low-voltage(%) 5.75 [2.31–10.64] 2.20 [0.55–8.43] 4.34[1.23–15.87] 4.47 [1.26–9.53] R/S ratio 0.54 [0.47–0.60] 0.63 [0.55–0.71] 0.25[0.02–0.40] -0.02 [-0.21–0.20] SP(%) 83.7 [75.7–89.3] 77.4 [67.3–87.3] 81.9[69.5–88.1] 80.6 [72.0–86.5] LDP(%) 4.0 [1.9–6.8] 3.8 [0.9–9.1] 1.6[0.3–5.5] 1.7 [0.6–4.1] FP(%) 1.3 [0.4–3.2] 1.4 [0.2–3.6] 0.7[0.2–2.5] 1.3 [0.4–2.5] FD(ms) 10.0 [8.0–14.0] 11.0 [9.0–14.0] 9.0[8.0–12.0] 9.0 [7.0–12.0] CB(%) 2.4 [1.2–3.8] 2.3 [1.0–5.1] 1.1[0.2–2.8] 0.7 [0.2–1.7] Conclusions: The signal fingerprint, consisting of quantified EGM features, including the R/S ratio of SPs, the relative frequency distribution of unipolar voltages, the proportion of low-voltage areas, the proportion of the different types of EGMs and durations of LDP and FDP, may serve as a diagnostic tool to determine the severity and extensiveness of conduction inhomogeneity. Further studies are required to determine whether the signal fingerprint can be used to identify patients at risk for AF onset or progression.